Pengembangan Aplikasi Pemantauan dan Rekomendasi Kesehatan Lansia dengan Metode Content-Based Filtering dengan Sistem Notifikasi untuk Keluarga - Fauzan Natsir; Redo Abeputra Sihombing; Andi Dwi Pangestu (Jurnal Ilmu Komputer, Teknologi Dan Informasi, 2025)
The growth of the elderly population in Indonesia continues to increase significantly; however, access to adequate healthcare services remains a major challenge that has yet to be resolved. This situation is further compounded by the lack of continuous monitoring and the limited ability of families to detect changes in the health condition of elderly individuals at an early stage. This study aims to develop a web and mobile-based application that integrates real-time elderly health monitoring features with a health recommendation system using the Content-Based Filtering (CBF) method, equipped with an automatic notification system for family members as an effort to improve responsiveness to emergency conditions and significant health changes. The development method employed is the Prototype Model with an iterative approach, enabling continuous feature refinement based on user feedback at each development cycle. The CBF algorithm utilizes the comprehensive individual health profiles of elderly users, encompassing medical history, vital data, and daily lifestyle patterns, to generate personalized and relevant recommendations for each user. System testing was conducted using the Black Box Testing method for functional validation and the System Usability Scale (SUS) for evaluating the usability of the application interface. The test results indicate that all system functions operate in accordance with the defined specifications, with a weighted average SUS score of 75.9, which falls within the Good category. This application is expected to strengthen collaboration between families and healthcare professionals in efforts to improve the quality of life and overall well-being of the elderly in Indonesia in a sustainable manner.